Social change and human development concept and results - Silbereisen, R. K. (Rainer K.) 1944-; Chen, Xinyin (Sage, 2010)
"Today's world is characterized by a set of overarching trends that often come under the rubric of social change. In this innovative volume, Rainer K. Silbereisen and Xinyin Chen bring together, for the first time, international experts in the field to examine how changes in our social world impact our individual development.Divided into four parts, Human Development and Social Change explores the major socio-political and technological changes that have taken place around the world - from the rapid upheavals in 1990s Europe to the gradual changes in parts of East Asia - and explains how these developments interplay with human development across the lifespan."-Provided by publisher.